Association of mean arterial pressure with all-cause and cardiovascular mortality in young adults - Sun, Shuo; Lo, Kenneth; Liu, Lin; Huang, Jiayi; Feng, Ying Qing; Zhou, Ying-ling; Huang, Yu-Qing (Postgraduate medical journal, 2020)
BackgroundMean arterial pressure (MAP) is a predictor of all-cause and cardiovascular disease (CVD) mortality in middle-aged population and elderly, but less evidence has been shown in young adults.ObjectivesWe examined the associations of MAP with all-cause and CVD mortality in young adults aged between 18 and 40 years.MethodsData were from the National Health and Nutrition Examination Survey (1999–2006) and participants were followed up to 31 December 2015. MAP was categorised by quartiles. Multivariable Cox proportional hazards models and Kaplan-Meier survival curves were performed to estimate the association between MAP, all-cause and CVD mortality.ResultsThere were a total of 8356 (4598 women (55.03%)) participants with the mean age of 26.63±7.01 years, of which 265 (3.17%) and 10 (0.12%) cases of all-cause and cardiovascular mortality occurred during a median follow-up duration of 152.96±30.45 months, respectively. There was no significant difference in the survival rate by MAP quartiles (p=0.058). When MAP was treated as a continuous variable, the multivariable adjusted HRs for all-cause and CVD mortality were 1.00 (95% CI 0.96 to 1.04; p=0.910) and 0.94 (95% CI 0.77 to 1.14; p=0.529), respectively. When using the lowest quartile (Q1) as referent, the adjusted HRs for all-cause mortality from Q2 to Q4 were 1.16 (95% CI 0.56 to 2.42), 1.06 (95% CI 0.48 to 2.32) and 0.91 (95% CI 0.37 to 2.24; p for tend was 0.749) after adjusting for potential confounders.ConclusionThere was no significant association of MAP with all-cause and CVD mortality in young adults with a relatively short follow-up time.